2015
DOI: 10.1159/000381479
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Patients' Quality of Life in Mixed States: A Preliminary Qualitative Study

Abstract: Background: Approximately 20% of patients with bipolar disorder experience mixed states. Mixed states are associated with more comorbidity, poorer treatment response and prognosis, increased relapse rate, and decreased functioning. This study aimed to produce in-depth knowledge about bipolar patients' quality of life (QoL) and functioning related to mixed states. Sampling and Methods: This study used qualitative research methods. A semi-structured interview guide based on a literature study was applied in inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In contrast to previous studies, we found no association between mixed mood and either quality of life or functioning in the present study. Further, previous studies have suggested that mixed symptoms in patients with bipolar disorder are associated with poorer prognosis and aggravated long‐term course of illness, including poorer treatment response , increased risk of relapse , decreased quality of life , decreased functioning and increased risk of suicide . In addition, in exploratory analyses we found results suggesting that there is no association between subsyndromal clinically rated manic symptoms and functioning and quality of life respectively.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…In contrast to previous studies, we found no association between mixed mood and either quality of life or functioning in the present study. Further, previous studies have suggested that mixed symptoms in patients with bipolar disorder are associated with poorer prognosis and aggravated long‐term course of illness, including poorer treatment response , increased risk of relapse , decreased quality of life , decreased functioning and increased risk of suicide . In addition, in exploratory analyses we found results suggesting that there is no association between subsyndromal clinically rated manic symptoms and functioning and quality of life respectively.…”
Section: Discussionmentioning
confidence: 39%
“…However, a substantial proportion of patients with bipolar disorder experience subsyndromal symptoms on a daily basis, and this has been associated with impaired functioning, increased risk of hospitalization, high risk of relapse, and comorbid substance use disorder , overall emphasizing the chronic and serious nature of bipolar disorder. Within bipolar disorder, mixed states and mixed symptoms represent a complex and heterogenous syndrome which has been associated with overall poorer prognosis and aggravated long‐term course of illness, including poorer treatment response , increased risk of relapse , decreased quality of life , decreased functioning and increased risk of suicide .…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 43 44 45 ] Only one study so far reported that functioning of patients in key life domains such as self-esteem, love and social life, family, physical well-being, and working capability was affected in mixed states of BD. [ 46 ] This study has found that the effect of the disorder per say on the self-esteem seems to be lasting even after illness is remitted.…”
Section: Discussionmentioning
confidence: 99%
“…This study was in line with study done in UK. Participants with higher educational attainment appeared to have good quality of life [22][23][24][25][26][27][28][29][30][31][32]. People with bipolar disorder have poor quality of life than the general population which is in line with study done in pristine, England [33].…”
Section: Discussionmentioning
confidence: 54%